Contextual Science Learning using Smartphone Audio Sensor Application (Phyphox) on Restitution Coefficient Measurement - Wijayanti, Arfilia; Marwoto, Putut; Wiyanto, Wiyanto; Ridlo, Saiful; Parmin, Parmin (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
The cognitive development of elementary school student are at a concrete operational stage, so that prospective elementary school teachers must have knowledge and experience in managing contextual and meaningful learning. The obstacle to the implementation of practicum while online learning during the Covid-19 pandemic, so an alternative method is needed to carried out in a home experiment. In the daily life of the students, collision events are often encountered. Many kinds of playing ball (i.e., tennis balls, basketball, and ping-pong ball) are examples of collision events. This research aims are to develop material content elastic collision experiments of contextual science learning for prospective teachers using the Phyphox application. The Research and Development (R and D) through ADDIE design has been applied to achieve the objectives of this research. The stages of this research were carried out through the stages of Analysis, Design, Development, Implementation and Evaluation. This research has produced a material content elastic collision experiments of contextual science learning for prospective science teachers through using the Phyphox application. The average percentage of material expert validation results related to indicator of content quality, content compliance and content language is 93.33%. The experimental results show that the coefficient of restitution of the small basketball on the ceramic floor is 0.848; for tennis balls 0.716 and for ping-pong balls is 0.836. The collision for the three types of the balls with the floor are classified as partially elastic collisions. It can be concluded that the material content elastic collision experiments of contextual science learning for prospective science teachers using the Phyphox application are in very feasible criteria and valid to be implemented in basic science concept lectures. The implication of this research indicates that smartphone-based experiments using phyphox application motivate and makes various science experiments more accessible with simple methods to analyze experiment data. Home experiment activity using Phyphox application is recommended to help students to describe and determine the type of collision, determine the energy lost during a collision and the coefficient of restitution, draw a graph of the relationship between height and time in a contextual and meaningful way of science learning activity.